Investigating the Effect of Orthodontic Treatment on Salivary IgA Levels - Arian Hesam Arefi; Omid Khorshidi; Abolfazl Hosseinabadi (Journal of Craniomaxillofacial Research)
Introduction: One of the most important and complex functions of saliva is its defensive role, which is mainly performed by immunoglobulins, especially secretory IgA. This study investigated the effect of orthodontic treatment on changes in the salivary levels of IgA. Materials and Methods: Forty patients undergoing orthodontic treatment were examined in two fixed and removable groups. Saliva collection was done in three stages: before orthodontic treatment and three and six months after orthodontic treatment. Salivary IgA level was measured using the ELISA method. First, the salivary samples were centrifuged, and then the amount of IgA in the upper part of the solution was determined using the ELISA method. Results: In the fixed and removable orthodontic treatment groups, the amount of salivary IgA before treatment, three months after treatment, and six months after treatment, according to ANOVA, showed a significant difference in the mean of salivary IgA levels. Conclusion: With the start of orthodontic treatment, one can witness an increase in the defense mechanisms of saliva, as evidenced by an increase in the amount of IgA, with differences between fixed and removable orthodontic treatments. Keywords: Orthodontic treatment; Saliva; IgA.